Improving research milieu in the medical colleges in India: Challenges and solutions - Gitanjali Batmanabane; Rituparna Maiti (Indian Journal of Rheumatology)
The quality of the research output of an individual or an institution is the currency by which the caliber of a scientist or an educational institution is judged by peers. In India, the quality of research conducted in medical colleges and scientific institutions leaves much to be desired. The educational system in schools does not foster creativity and originality. The medical undergraduate training focuses mainly on making medical students good clinicians and does not have the curricular time for research. At a postgraduate level, residents are overburdened with clinical work or stifled by the lack of ideas and enthusiasm of their guides. The Indian Council of Medical Research has introduced a short-term studentship for undergraduate students and a research grant for postgraduate students in a bid to encourage research. The National Medical Commission has made it mandatory for postgraduates and faculty to undergo online training in research methodology. The thesis has been a part of the postgraduate curriculum with the idea that as the resident does the project, they will also learn how to do research. In a bid to translate the thesis into publications, many professional bodies conduct workshops and courses during conferences on various aspects of scientific writing. However, many postgraduates do not want to spend time in an activity that is seen as nonrewarding. Unless a drastic change in the postgraduate curriculum is made and the issue of research training is adequately addressed, along with a change in the outlook of faculty, the status quo is likely to continue.